Effectiveness of Dupa Aromatherapy Incense Ethnoscience-Based TAPPS on Written Communication Skills - Aisah Nur' Aini; Suciati Suciati; Budi Utami; Kadek Dwi Hendratma; Bayu Antrakusuma (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aimed to investigate the effectiveness of the ethnoscience-based Think Aloud Pair Problem Solving (TAPPS) model using aromatherapy incense in improving students’ written communication skills on elements, compounds, and mixtures. This study employed a quasiexperimental method with a pretest–posttest nonequivalent control group design. The sample consisted of class VIII A as the experimental group and class VIII B as the control group at SMP N 6 Surakarta, selected using cluster random sampling. The research instrument was an experimental report assessment rubric that had undergone content validity testing. Data were analyzed using descriptive statistics, prerequisite tests, an Independent Sample t-test, and effect size analysis. The results showed a significant difference between the experimental and control groups. The experimental class achieved higher written communication skills than the control class, with a large effect size (d = 0.747). Improvements were observed in effective introduction, main objectives and ideas, report clear, structured and coherent, appropriate technical language, and grammar. It can be concluded that the ethnoscience-based TAPPS model effectively improves students’ written communication skills.